Abatacept and T-cell costimulation blockade—shifting the paradigm in the prevention of graft-versus-host disease - Chakrabarti, Suparno; Jaiswal, Sarita Rani (Frontiers in Hematology, 2023)
Despite advances in transplantation techniques and immunosuppressive therapies, graftversus-host disease (GVHD) remains a significant cause of morbidity and mortality, necessitating innovative strategies for its prevention. T cell activation plays a crucial role in the pathogenesis of GVHD, and T cell costimulation blockade (COSBL) has emerged as a promising approach to prevent this devastating condition. This review aims to explore the concept of T cell costimulation blockade and its potential as a paradigm-shifting strategy in the prevention of GVHD, in the context of the existing modalities for prevention of GVHD and the preclinical and clinical studies on COSBL. The unique property of abatacept (CTLA4Ig) is not just limited to dampening T cell activation. The salutary effect of abatacept on natural killer cells and Tregs alike, provide a unique opportunity to dissociate T cell mediated GVHD from NK cell mediated graft-versus-leukemia. Further research is warranted to explore other modalities of COSBL, determine optimal dosing and combinations for COSBL, and identify predictive biomarkers for patient stratification, ultimately enhancing the way for improved outcomes in HCT recipients.